Let ( v , v , a ) be the scalar speed, the vector velocity, and the vector acceleration of an object, respectively. If, at a particular instant, v = ( 1 , 2 , 3 ) and a = ( − 1 , − 1 , 2 ) , determine the rate of change of the speed ( d t d v ) .
Note: The vector acceleration is the time-derivative of the vector velocity
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I took an unnecessarily long route to find the asnwer. This is a more elegant method. Thanks
Consider the following:
V = v x i ^ + v y j ^ + v z k ^ a = a x i ^ + a y j ^ + a z k ^ S = ∣ V ∣ = v x 2 + v y 2 + v z 2
Now, the velocity vector:
V = S ⎝ ⎛ v x 2 + v y 2 + v z 2 v x i ^ + v x 2 + v y 2 + v z 2 v y j ^ + v x 2 + v y 2 + v z 2 v z k ^ ⎠ ⎞
⟹ V = S V ^ ⟹ d t d V = a = d t d S V ^ + S d t d V ^ … ( 1 )
Consider:
d t d V ^ = d t d ⎝ ⎛ v x 2 + v y 2 + v z 2 v x ⎠ ⎞ i ^ + d t d ⎝ ⎛ v x 2 + v y 2 + v z 2 v y ⎠ ⎞ j ^ + d t d ⎝ ⎛ v x 2 + v y 2 + v z 2 v x ⎠ ⎞ k ^
Crunching out the derivatives and computing the following relation results in:
a − S d t d V ^ = v x 2 + v y 2 + v z 2 v x ( a x v x + a y v y + a z v z ) i ^ + v x 2 + v y 2 + v z 2 v y ( a x v x + a y v y + a z v z ) j ^ + v x 2 + v y 2 + v z 2 v z ( a x v x + a y v y + a z v z ) k ^ a − S d t d V ^ = v x 2 + v y 2 + v z 2 a x v x + a y v y + a z v z ( v x i ^ + v y j ^ + v z k ^ ) a − S d t d V ^ = v x 2 + v y 2 + v z 2 a x v x + a y v y + a z v z V a − S d t d V ^ = v x 2 + v y 2 + v z 2 a x v x + a y v y + a z v z V ^
The above expression, when compared to (1), shows that:
d t d S V ^ = v x 2 + v y 2 + v z 2 a x v x + a y v y + a z v z V ^ ⟹ d t d S = v x 2 + v y 2 + v z 2 a x v x + a y v y + a z v z
Plugging in numbers gives:
v x = 1 ; v y = 2 ; v z = 3 ; a x = − 1 ; a y = − 1 ; a z = 2
d t d S = 1 4 3
Note:
d t d S = v x 2 + v y 2 + v z 2 a x v x + a y v y + a z v z d t d S = a ⋅ V ^
I do not see the intuition behind this yet.
Problem Loading...
Note Loading...
Set Loading...
I came upon this today while solving another problem. It's kind of a cool property. @Karan Chatrath also has this in his solution.
v = v x 2 + v y 2 + v z 2 d t d v = 2 1 ( v x 2 + v y 2 + v z 2 ) − 1 / 2 ( 2 v x a x + 2 v y a y + 2 v z a z ) = v v ⋅ a